A review on quality control, toxicity and clinical application of Amomum tsao-ko Crevost & Lemarié - Zhong-hui Pu; Bao-shan Wang; Si-yuan Zhang; Feng-hui Sun; Min Dai (Elsevier, 2022)
The dried fruit of Amomum tsao-ko Crevost & Lemarié, a perennial herb of Cardamom in Zingiberaceae, has been widely used in food and as a folk medicine. It is used not only as an important food additive and spice for removing peculiar smell and improving taste, but also as a traditional Chinese medicine with significant efficacy in treating many kinds of disorders. Based on the high edible and medicinal value, large amounts of investigation have been reported for A. tsaoko in the past several years. This review specifically summarises its quality control, toxicology and clinical application, about which no literature had systematically reviewed, based on our best acknowledge. The current quality control of A. tsaoko is based on the content of volatile oil, which should be no less than 1.4% according to the Pharmacopoeia of the People's Republic of China (2020 edition), while a more possible Q-Markers should be developed to focus on either a specific bioactive ingredient or a component correlated with a certain clinical efficacy. Toxicity research suggests that A. tsaoko actually belongs to the non-toxic substance, although citral and 1,8-cineole, two main components of A. tsaoko, is hepatotoxic for the former and displays low acute toxicity and sub-chronic oral toxicity for the latter, but no obviously accumulative toxicity has so far been discovered for A. tsaoko. In clinical practice, A. tsaoko is often used in treatment of dampness/cold resistance, malaria, vomiting, fullness and epigastric distension across additional disorders, such as SARS, COVID-19 and hepatitis.